Surgical Loupe at 4.0× Magnification in Pancreaticoduodenectomy—Does It Affect the Surgical Outcomes? A Propensity Score–Matched Study. (April 2019) - El Shobary, Mohamed; El Nakeeb, Ayman; Sultan, Ahmad; Ali, Mahmoud Abd El Wahab; El Dosoky, Mohamed; Shehta, Ahmed; Ezzat, Helmy; Elsabbagh, Ahmed M.
Background. There is paucity of data about the impact of using magnification on rate of pancreatic leak after pancreaticoduodenectomy (PD). The aim of this study was to show the impact of using magnifying surgical loupes 4.0× EF (electro-focus) on technical performance and surgical outcomes of PD. Patients and Method. This is a propensity score–matched study. Thirty patients underwent PD using surgical loupes at 4.0× magnification (Group A), and 60 patients underwent PD using the conventional method (Group B). The primary outcome was postoperative pancreatic fistula. Secondary outcomes included operative time, intraoperative blood loss, postoperative complications, mortality, and hospital stay. Results. The total operative time was significantly longer in the loupe group ( P = .0001). The operative time for pancreatic reconstruction was significantly longer in the loupe group ( P = .0001). There were no significant differences between both groups regarding hospital stay, time to oral intake, total amount of drainage, and time of nasogastric tube removal. Univariate and multivariate analyses demonstrated 3 independent factors of development of postoperative pancreatic fistula: pancreatic duct <3 mm, body mass index >25, and soft pancreas. Conclusion. Surgical loupes 4.0× added no advantage in surgical outcomes of PD with regard to improvement of postoperative complications rate or mortality rate.